Complexity, Capacity, and Budget Punctuations. Issue 2 (16th February 2016) - Epp, Derek A.; Baumgartner, Frank R.
Abstract : The budgeting literature has long focused on "institutional friction" as a cause of ubiquitous punctuated equilibrium (PE) findings. A recent wave of scholarship looks to identify specific institutional mechanisms that affect the number of punctuations in policy outputs. We contribute to this growing body of research by focusing on the complexity of the institutional environment surrounding a policy area as well as that of the government as a whole. These factors have opposite effects: the more complex a policy area, the greater the likelihood of extreme spending changes. But, higher institutional capacity in general leads to greater stability. To test these ideas, we develop a novel index of budgetary change that balances the conceptual importance of extreme changes while analyzing the entire distribution of budget changes, not only the tails. In addition, we also demonstrate that findings are robust to a number of important distinctions, such as between series associated with slowly moving demographic trends or quickly moving stochastic events. We, therefore, demonstrate the robustness of important findings from the established literature, add a new measure of the dependent variable, and push the literature forward with a new focus on issue complexity and institutional capacity.